Недовольство населения пенсионной реформой: гендерный аспект - Григорьева, Ирина; Квасова, Олеся (ЖУРНАЛ СОЦИОЛОГИИ И СОЦИАЛЬНОЙ АНТРОПОЛОГИИ, 2019)
The article provides an assessment of the pension reform of 2018 in Russia and raises a number of issues. The main change in the pension system is the increase in the retirement age. This measure is the main in international practice. As a rule, this is implemented at a slower pace than half a year. Recent reforms in the area of pensions have generated various possible ways for the development. We will consider options for changing the pension system, not included in the Pension Reform. Other options (increase in seniority or tax from enterprises) are more difficult to implement, since many companies are in the shadow sector. Women found themselves in a difficult position because of the difficulties in finding a job after 45 years. They retired and raised their grandchildren, after which they cannot return to work. Employment at a later age is growing in many developed countries. The elderly find work as they improve their skills, adapt to new conditions and part-time employment. Studies of older people’s labour potential in Russia suggest that the situation with post-retirement employment will improve once people with sufficient educational resources. At the moment, our government offers control over employers. It is important to find out which solutions for the pension issue could be considered? What are the risks and opportunities for women of pre-retirement age? These and other points were revealed by us in the article.